The effect of respiratory muscle training on fin-swimmers` performance - Vasickova, J.; Neumannova, K.; Svozil, Z. (Journal of Sports Science & Medicine, 2017)
Although respiratory muscle functions can influence swimming performance, respiratory muscle training (RMT) is not routinely used for improving fin-swimmers´ performance. The aim of our study was to verify the benefit of a one month of RMT in young fin-swimmers. We assessed the effect of this training on respiratory muscles and on maximal underwater swimming distance. 28 fin-swimmers were randomly divided into an experimental group (EG) and a control group (CG). The study finished with 20 fin-swimmers (EG: n = 12; average age 12.0; weight 47.4 kg; height 1.58 m; CG: n = 8; age 11.5; weight 49.6 kg; height 1.53 m). Both group performed regular swimming training, during which the EG used Threshold PEP (positive expiratory pressure) and IMT (inspiratory muscle trainer) for RMT for one month. After one-month washout period, the CG also performed RMT. RMT showed significant improvement of inspiratory muscles in both groups (Z = <1.96; 2.59>; p < 0.05). Significant improvement was observed also in apnoea (AP) max (ZCG = 2.03; p < 0.05; ZEG=2.93; p < 0.01). A long-term effect was observed in the respiratory muscle strength and AP max in the EG (ZEG = 2.52; p < 0.05). RMT in fin-swimmers improves both respiratory muscle strength and the performance in AP max.